Teachers' Reported Knowledge and Implementation of Research-Based Classroom and Behavior Management Strategies. (July 2017) - Moore, Tara C.; Wehby, Joseph H.; Oliver, Regina M.; Chow, Jason C.; Gordon, Jason R.; Mahany, Laura A.
Teachers' reported knowledge about and implementation of research-based classroom and behavior management strategies were examined. A total of 160 elementary teachers from two districts in different regions of the same state completed the researcher-developed Survey of Classroom and Behavior Management . On average, teachers reported to be somewhat knowledgeable and to implement somewhat all of the 10 sets of research-based strategies included in the survey. Teachers appeared to be most knowledgeable and more frequently implement prevention practices but less knowledgeable and less frequently implement individualized behavioral intervention strategies. Teachers' reported knowledge was correlated with their reported use of strategies. There was a significant difference in reported knowledge across the two districts. Implications are provided for areas of future research and for using the survey to identify targets for improved pre-service and inservice training and support.